KODE ETIK HAKIM MAHKAMAH AGUNG DAN MAHKAMAH KONSTITUSI - Firman Agus Faisal; Muhammad Haidir Ali Hafid; Siti Khotimah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article discusses the professional ethics of judges in the Supreme Court and Constitutional Court of Indonesia. Judges play a crucial role in the enforcement of law and justice and bear a high moral responsibility. The article explains various aspects of ethics that judges must uphold, including personal ethics, ethics in the performance of duties and positions, ethics in service, and ethics in relationships with fellow judges. This research also highlights the importance of supervision by the Judicial Commission to maintain integrity and public trust in the judicial system. The conclusion of this article emphasizes that the code of ethics is not only a moral guideline but also a tool to address legal issues in society. Several suggestions are proposed to enhance supervision and ethical education for judges to strengthen the integrity of the judiciary in Indonesia.